Associations between emotion recognition and autistic and callous‐unemotional traits: differential effects of cueing to the eyes. (12th December 2022) - Carter Leno, Virginia; Pickard, Hannah; Cybulska, Liliana; Smith, Tim; Munafo, Marcus; Penton‐Voak, Ian; Simonoff, Emily; Pickles, Andrew; Bedford, Rachael
Abstract : Background: Although autism and callous‐unemotional (CU) traits are distinct conditions, both are associated with difficulties in emotion recognition. However, it is unknown whether the emotion recognition difficulties characteristic of autism and CU traits are driven by comparable underpinning mechanisms. Methods: We tested whether cueing to the eyes improved emotion recognition in relation to autistic and CU traits in a heterogeneous sample of children enhanced for social, emotional and behavioural difficulties. Participants were 171 ( n = 75 male) children aged 10–16 years with and without a diagnosis of autism ( n = 99 autistic), who completed assessments of emotion recognition with and without cueing to the eyes. Parents completed the assessment of autistic and CU traits. Results: Associations between autistic and CU traits and emotion recognition accuracy were dependent upon gaze cueing. CU traits were associated with an overall decrease in emotion recognition in the uncued condition, but better fear recognition when cued to the eyes. Conversely, autistic traits were associated with decreased emotion recognition in the cued condition only, and no interactions between autistic traits and emotion were found. Conclusions: The differential effect of cueing to the eyes in autistic and CU traits suggests different mechanisms underpin emotion recognition abilities. Results suggest interventions designed to promote looking to the eyes may be beneficial for children with CU traits, but not for children with autistic characteristics. Future developmental studies of autism and CU characteristics are required to better understand how different pathways lead to overlapping socio‐cognitive profiles.